The information use environment of abused and neglected children - J.A. Hersberger; A.L. Murray; S.MA. Sokoloff (Information Research: An International Electronic Journal)
Introduction. When children are adjudicated by a court of law as being maltreated, they are summarily removed from their homes, resulting in a disruption of their daily lives. This pilot study examines the context in which maltreated children seek and use information to cope with this stressful period of their lives. Method. This study applies Taylor's four components of information use environments to look at the user and the uses of information and the contexts within which those users make choices about what information is useful to them at particular times. Analysis. The characteristics of foster children as a population are examined and the settings in which such children seek information are described. The problems experienced by children, which are linked to information seeking, are articulated as are problem resolutions. Results. The most important finding of this study is the determination that there are three clearly differentiated phases of information needs and seeking corresponding to the three phases of adjustment the children experience. Conclusion. Understanding problem phases underpinning everyday life contexts in foster care environments afford support personnel who provide information to these children better insights into what helps and what results in increasing anxiety or causes more trauma.